Effect of reduced fungicide doses on control of soybean Asian rust and bean yield - Feliciani Barbosa, Giselle [UNESP]; Da Cruz Centurion, Maria Aparecida Pessôa [UNESP]; Tardivo Marin, Beatriz [UNESP]; Feliciani Barbosa, Grazielle (My University, 2013)
One of the diseases of greatest importance for soybean [Glycine max (L.) Merrill] crops is the soybean Asian rust, caused by the fungus Phakopsora pachyrhizi Sydon & P. Sydon. One of the main methods of control is through the use of chemical fungicides. The objective of this study was to evaluate the effects of reduced doses of the fungicides azoxystrobin +ciproconazol +mineral oil and tebuconazol, with two application intervals (10 and 20 days), on two soybean cultivars [NK-412113 (V Max) and MG/BR-46 (Conquista)], for the control of soybean rust, as well as their effects on yield. A field assay was conducted during spring-summer 2006/2007. Disease severity assessment was done at 10 days intervals, before fungicide spraying, using a diagrammatic scale. For the early cultivar (NK-412113), the use of reduced fungicide doses did not change disease severity. For the semi early cycle cultivar (MG/BR-46), reduced doses were not significantly different from the recommended doses for soybean rust control. A yield increase was observed in cultivar MG/BR-46 with fungicide spraying, but not for NK-412113. When the disease affects plants at critical stages related to the formation of pods and grains, fungicide treatments azoxystrobin +ciproconazol, in their reduced doses, can also provide efficient control of the disease, with lower severity and higher yields.
Keywords: Application intervals; Asian rust; Chemical control; Glycine max; Pests; Phakopsora pachyrhizi; Soybean